Early Childhood Development Within Multigenerational Caregiving Systems in Central Kalimantan - Aghnaita Aghnaita; Neela Afifah; Ervina Ervina (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Multigenerational families living under one roof create a unique caregiving environment that can influence early childhood development in both positive and negative ways. This study aims to describe the developmental characteristics of young children living in multigenerational family settings in Central Kalimantan. A descriptive qualitative approach was employed, with research conducted in two regions North Barito Regency and Murung Raya Regency. Primary data were collected from eight multigenerational families, consisting of four families in Teweh Baru District and four families in Puruk Cahu City. The findings reveal that children engage in diverse daily activities such as independent play, peer play, watching television, and using digital devices. Parents and grandparents also introduce early moral values, religious practices, and basic academic skills. For children attending preschool, formal learning activities also contribute to their developmental experiences. These daily routines collectively shape multiple domains of development, including cognitive, motor, language, social, and emotional growth. The study highlights that family dynamics, caregiving practices, and environmental stimulation within multigenerational households play a significant role in supporting or constraining early childhood development.